Vanadium(IV) coordination complexes with excellent biological activities: a synthetic, characterization, and density functional theory approach. Issue 5 (30th June 2022) - Sharma, Sonika; Das, Debasish; Sadhu, Biswajit; Sharma, Neeraj
Abstract: A set of new oxidovanadium(IV) complexes, [VO(4-NO2 C6 H4 CH = CHCONHO)2 ] (1 ), [VO(4-NO2 C6 H4 CH = CHCONHO)2 (2–CNC5 H4 N)] (2 ) and [VO(4-NO2 C6 H4 CH = CHCONHO)2 (4-CNC6 H4 NH2 )] (3 ), have been synthesized and characterized by different analytical techniques (magnetic susceptibility, molar conductivity, elemental analysis) and spectroscopic techniques, viz. FTIR, UV–vis, EPR, and mass spectrometry. The magnetic susceptibility, EPR, and ESI-MS data indicate that 1 exists as monomer and a distorted square pyramidal geometry around vanadium is ascertained. The electrochemical study of 1 has shown that it is electrochemically active exhibiting VO V /VO IV quasi-reversible redox couple. The biological activity of 1 –3 has been studied against various pathogenic bacteria Staphylococcus epidermidis, Klebsiella pneumoniae, Staphylococcus aureus, Escherichia coli, Salmonella paratyphi, and Salmonella typhi, and fungi Brachypsectra fulva, Candida albicans, and Fusarium oxysporum by minimum inhibitory concentration (MIC) method. In some cases, the synthesized complexes showed superior antibacterial and antifungal activity than the well-known standard drugs tetracycline hydrochloride and fluconazole. The cytotoxicity of 1 –3 has been studied on a human cervix carcinoma HeLa cell derivative (mammalian transformed cell line Hep2c) by MTT assay. Density functional theory (DFT) studies have been carried out to determine their relative free energy of formation and optimized molecular structures of 1 –3 . Time-dependent density functional theory (TD-DFT) based calculations have been performed to find out the frontier molecular orbitals and corroborate with the experimentally observed electronic transitions of 1 . Other parameters like HOMO, LUMO energies, and global reactivity descriptors clearly support higher biological activity of 2 and 3 than 1 . Graphical Abstract: UF0001